Penyempurnaan Substansi Pedoman Penyusunan Rencana Tata Ruang Wilayah (RTRW) Provinsi, Kabupaten, Kota - Eko Budi Santoso (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2008)
Since implementing of Spatial Planning Act Number 26 year of 2006, few regulation in spatial planning should be changed. One of these regulation is Manual in making spatial planning in province, regency, and city in Indonesia. In order to get harmony in spatial planning between national planning, regional (province) and local (regency, and city) planning, then is made the manual in making spatial planning in province, regency, and city planning in Indonesia. There was old manual in making spatial planning in province, regency, and city planning in Indonesia, at Ministrrial Decree number 327/M/KPTS/2002. After implementing of spatial planning Act number 26 year of 2006, end concerning with changing in other act, regulation, decree, and also empirical reality in tailoring local spatial planning, the old one should be revised. This paper try to explore about the substance which needed to be revised or harmonized in the new/revised regulation. The final hope of existence of new regulation and implementation of the regulation is to achieve the goal of national spatial planning.